2015
DOI: 10.1007/s11103-015-0338-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gene expression profiles and responses to zinc chloride among inter- and intraspecific hybrids with growth abnormalities in wheat and its relatives

Abstract: Hybrid necrosis is a well-known reproductive isolation mechanism in plant species, and an autoimmune response is generally considered to trigger hybrid necrosis through epistatic interaction between disease resistance-related genes in hybrids. In common wheat, the complementary Ne1 and Ne2 genes control hybrid necrosis, defined as type I necrosis. Two other types of hybrid necrosis (type II and type III) have been observed in interspecific hybrids between tetraploid wheat and Aegilops tauschii. Another type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
(81 reference statements)
1
7
0
Order By: Relevance
“…In most types of wheat hybrid necrosis, defense-related genes are dramatically up-regulated under both normal temperature and LT [14,17]. To validate the microarray data in the type II necrosis lines, qRT-PCR was conducted for two defense-related genes, PR1 and PR4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most types of wheat hybrid necrosis, defense-related genes are dramatically up-regulated under both normal temperature and LT [14,17]. To validate the microarray data in the type II necrosis lines, qRT-PCR was conducted for two defense-related genes, PR1 and PR4 .…”
Section: Resultsmentioning
confidence: 99%
“…Cell death occurs gradually from older to younger tissues in the hybrid lines showing type III necrosis, similarly to type I and type IV necrosis observed in other cross combinations of wheat [17], whereas a necrotic phenotype of type II necrosis lines is induced by low temperature (LT) conditions [14]. In addition, in the type II necrosis lines, stem elongation is markedly inhibited, and new leaf expansion is delayed under LT [16].…”
Section: Introductionmentioning
confidence: 96%
“…Cyanine 3-labeled cRNA was hybridized to the microarray, washed, and image scanning was performed according to our previous report (Takamatsu et al 2015). Scanned images were analyzed with Feature Extraction Software, Version 9.5 (Agilent Technologies) using default parameters to obtain background-subtracted and spatially detrended processed signal intensities.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Quantitative reverse transcription (qRT)-PCR analysis was performed using RNA isolated from crown tissues of WT, SGA and grass-clump dwarf plants. Each plant was grown at 24C under 16 h day length (182 μmol photons•m -2 •s -1 ), and total RNA extraction, first-strand cDNA synthesis and detection of transcript accumulation levels were performed according methods reported previously (Takamatsu et al 2015). Some of the examined genes were selected to validate their altered transcription levels in the SGA-and grass-clump dwarf-exhibiting ABU hybrids based on the microarray data.…”
Section: Quantitative Reverse Transcription (Qrt)-pcr Analysismentioning
confidence: 99%
“…Several studies have reported that PAL is involved in hybrid lethality among inter-and intraspecific hybrids in wheat and its relatives (Jiang et al 2008;Mizuno et al 2010Mizuno et al , 2011Takamatsu et al 2015). These studies have reported upregulation of PAL expression (Mizuno et al 2010(Mizuno et al , 2011Takamatsu et al 2015) and accumulation of PAL protein (Jiang et al 2008).…”
Section: Discussionmentioning
confidence: 99%